(untitled) (AYUSHDHARA, 2025)
Pregnancy is a beautiful and extraordinary phase of every female life either human or animal. Every day around 150 women die due to causes related to pregnancy and childbirth. Globally, it is estimated that 13% of maternal deaths occurred due to improperly performed procedures and unnecessary interventions. In pregnancy nutraceutical deficiency can lead to premature birth of child, neurological defects in the child and many more complications. In pregnancy many unusual clinical symptoms such as stress, anxiety, depression, mood swings, nausea, vomiting, easy fatigability, morning sickness, painful leg cramps, malaise in eyes, breathing problems, swollen ankle and feet, constipation, varicose vein, braxton hicks contraction and nutraceutical deficiency can lead to premature birth of child, neurological defects in the child and many more complications. Yoga & Ayurveda, are the Ancient and Holistic health science that have the power to keep the person healthy and manage many illnesses related to pregnancy and other general disorders. Daily practice of yoga and righteous use of Rasayana therapy enhances immunity, provide strength to body and helpful to deal with pregnancy related challenges, improve birth weight, decrease preterm labor, manage pain, reduced mental stress, anxiety and depression.